1979
DOI: 10.1136/bjo.63.11.735
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis for rubeosis iridis following central retinal vein occlusion.

Abstract: (Smith, 1961;Vannas, 1961;Laatikainen and Kohner, 1976). The stimulus for anterior segment neovascularisation is poorly understood but is thought to be related to severe retinal ischaemia (Smith, 1961;Ashton, 1961;Shilling and Kohner, 1976

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

1986
1986
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(22 citation statements)
references
References 10 publications
0
21
1
Order By: Relevance
“…NVG rarely results from non-ischaemic vascular occlusion (3,4,11) Neovascular glaucoma is known to develop in 8% of all CRVO, and 67-82% of ischaemic CRVO (3,4,(10)(11)(12). The high prevalence of hypertension in these subjects suggest the condition to be a predisposing systemic factor associated with CRVO in this series.…”
Section: Discussionmentioning
confidence: 86%
“…NVG rarely results from non-ischaemic vascular occlusion (3,4,11) Neovascular glaucoma is known to develop in 8% of all CRVO, and 67-82% of ischaemic CRVO (3,4,(10)(11)(12). The high prevalence of hypertension in these subjects suggest the condition to be a predisposing systemic factor associated with CRVO in this series.…”
Section: Discussionmentioning
confidence: 86%
“…CVOS study has reported that visual acuity outcome in CRVO was largely dependent on initial acuity. 11 Eyes with good initial vision have a good chance of maintaining excellent vision while a poor visual outcome is seen in those who had poor initial acuity.…”
Section: Crvo Groupmentioning
confidence: 99%
“…According to literature, incidence of rubeosis is 20% among CRVO. 11,12 Among ischaemic eyes, rubeosis with or without NVG occur in 45 to 80% and this usually develops by 4-7 months of the occlusion. Neovascularisation of optic disc or retina is a rare complication but has been reported in 24% of ischaemic CRVO.…”
Section: Crvo Groupmentioning
confidence: 99%
“…None of the non-ischemic CRVO patients developed NVG. Neo-vascular glaucoma was seen in 67 to 82 % of the ischemic CRVOs and in 1 % of the non-ischemic CRVO in other studies (Zegarra et al, 1979;Sinclair and Gragoudas, 1979). One patient developed vitreous hemorrhage.…”
Section: Resultsmentioning
confidence: 88%